Confirmation of ProMisE: A simple, genomics‐based clinical classifier for endometrial cancer - Talhouk, Aline; McConechy, Melissa K.; Leung, Samuel; Yang, Winnie; Lum, Amy; Senz, Janine; Boyd, Niki; Pike, Judith; Anglesio, Michael; Kwon, Janice S.; Karnezis, Anthony N.; Huntsman, David G.; et al. (Cancer, 2017)
BACKGROUND Classification of endometrial carcinomas (ECs) by morphologic features is irreproducible and imperfectly reflects tumor biology. The authors developed the Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE), a molecular classification system based on The Cancer Genome Atlas genomic subgroups, and sought to confirm both feasibility and prognostic ability in a new, large cohort of ECs. METHODS Immunohistochemistry (IHC) for the presence or absence of mismatch repair (MMR) proteins (to identify MMR deficiency [MMR‐D]), sequencing for polymerase‐ɛ (POLE) exonuclease domain mutations (POLE EDMs), and IHC for tumor protein 53 (p53) (wild type vs null/missense mutations; p53 wt and p53 abn, respectively) were performed on 319 new EC samples. Subgroups were characterized and assessed relative to outcomes. The prognostic ability of ProMisE was compared with that of current risk‐stratification systems (European Society of Medical Oncology [ESMO]). RESULTS ProMisE decision‐tree classification achieved categorization of all cases and identified 4 prognostic subgroups with distinct overall, disease‐specific, and progression‐free survival (P < .001). Tumors with POLE EDMs had the most favorable prognosis, and those with p53 abn the worst prognosis, and separation of the 2 middle survival curves (p53 wt and MMR‐D) was observed. There were no significant differences in survival between the ESMO low‐risk and intermediate‐risk groups. ProMisE improved the ability to discriminate outcomes compared with ESMO risk stratification. There was substantial overlap (89%) between the p53 abn and high‐risk ESMO subgroups; but, otherwise, there were no predictable associations between molecular and ESMO risk groups. CONCLUSIONS Molecular classification of ECs can be achieved using clinically applicable methods and provides independent prognostic information beyond established clinicopathologic risk factors available at diagnosis. Consistent, biologically relevant categorization enables stratification for clinical trials and/or targeted therapy, identification of women who are at increased risk of having Lynch syndrome, and may guide clinical management. Cancer 2017;123:802–13. © 2016 American Cancer Society. The prognostic ability of Cancer Genome Atlas–inspired, genomics‐based classification method in endometrial carcinomas is confirmed. This pragmatic system will enable more consistent categorization of tumors, stratification of clinical trials, more rapid identification of hereditary cancers, prognostic information, and potentially predictive applications to better guide clinical management. See also pages 728–30.